2016
DOI: 10.5194/bg-2016-444
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High resolution regional modeling of natural and anthropogenic radiocarbon in the Mediterranean Sea

Abstract: <p><strong>Abstract.</strong> A high-resolution dynamical model (NEMO-MED12) was use to give the first simulation of the distribution of radiocarbon (<sup>14</sup><i>C</i>) across the whole Mediterranean Sea. The simulation provides a descriptive overview of both the natural pre-bomb <sup>14</sup><i>C</i> and the entire anthropogenic radiocarbon transient gen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
(124 reference statements)
2
2
0
Order By: Relevance
“…Identification in Pore Waters 1623 (Tisnérat-Laborde et al 2013;Ayache et al 2017), which is consistent with the signature found in the OM for the nuclear period. As our results are slightly higher than the values of the surface ocean, another possible source of enriched DIC originating from the river plume is the impact of the nuclear power plants along the Rhône during the last 40 years.…”
Section: Sediment Pore Waterssupporting
confidence: 79%
See 2 more Smart Citations
“…Identification in Pore Waters 1623 (Tisnérat-Laborde et al 2013;Ayache et al 2017), which is consistent with the signature found in the OM for the nuclear period. As our results are slightly higher than the values of the surface ocean, another possible source of enriched DIC originating from the river plume is the impact of the nuclear power plants along the Rhône during the last 40 years.…”
Section: Sediment Pore Waterssupporting
confidence: 79%
“…This Δ 14 C OM result is probably linked to the deposition of enriched phytoplankton grown in marine surface waters during the nuclear period which is mineralized in the sediment and which transfers its isotopic signature to the pore water DIC. Evidence for this is the fact that the Δ 14 C values obtained in the NW Mediterranean Sea surface were around +90‰ in the 1970s and decreased to 60‰ in 2010 (Tisnérat-Laborde et al 2013; Ayache et al 2017), which is consistent with the signature found in the OM for the nuclear period. As our results are slightly higher than the values of the surface ocean, another possible source of enriched DIC originating from the river plume is the impact of the nuclear power plants along the Rhône during the last 40 years.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…CC BY 4.0 License. 2016a), tritium-helium-3 (Ayache et al, 2015) and 14 C (Ayache et al, 2016b). These evaluations 95…”
mentioning
confidence: 93%